2001
DOI: 10.1046/j.0956-540x.2001.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Network-magnetotelluric method and its first results in central and eastern Hokkaido, NE Japan

Abstract: Summary A new field observation technique based on the magnetotelluric (MT) method has been developed to determine deep and large‐scale 3‐D electrical conductivity distributions in the Earth. The method is named ‘Network‐MT’, and employs a commercial telephone network, to measure voltage differences with long dipole lengths ranging from 10 to several tens of kilometres. This observation configuration enables us to obtain the telluric field distribution with nearly continuous coverage over a target region. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 52 publications
1
36
1
Order By: Relevance
“…This suggests existence of conductive layer in east of Memanbetsu. Uyeshima et al (2001) suggested a significant coast effect in eastern Hokkaido based on the observation by the networkmagnetotelluric (network-MT) method. Consideration of underground conductivity is necessary to understand the measured GIC data as a future work.…”
Section: Estimation Of Gic and Discussionmentioning
confidence: 99%
“…This suggests existence of conductive layer in east of Memanbetsu. Uyeshima et al (2001) suggested a significant coast effect in eastern Hokkaido based on the observation by the networkmagnetotelluric (network-MT) method. Consideration of underground conductivity is necessary to understand the measured GIC data as a future work.…”
Section: Estimation Of Gic and Discussionmentioning
confidence: 99%
“…The NMT method was developed and first applied in central and eastern Hokkaido, northeastern Japan (NEJ), by Uyeshima (1990) and Uyeshima et al (2001). Yamaguchi et al (1999) and Satoh et al (2001) applied the method in eastern Shikoku, SWJ, and eastern Hokkaido, NEJ, respectively.…”
Section: Modification Of the Nmt Methodsmentioning
confidence: 99%
“…Theoretical details describing the procedure of the network-MT analysis are given in Uyeshima et al [2001] and Uyeshima [2007]. This section explains the main data-processing steps applied in the present study.…”
Section: Data Processing Of Network-magnetotelluric Observationsmentioning
confidence: 99%
“…We here describe the electrical resistivity structure beneath the Kyushu subduction zone in the Southwest Japan arc (Figure 1), which was determined using measurements recorded by the network-magnetotelluric (network-MT) sounding method [Uyeshima et al, 2001]. Various geophysical methods can be applied in the observation of subsurface structures, depending on the target of interest (e.g., fluids triggering partial melt below volcanoes or earthquake-triggering fluids).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation